Humification degree and its relationship with some soil physical characteristics on robusta coffee (Coffea canephora) plantation - M J N F I A Putra; S Soemarno; R Suntari (Journal of Degraded and Mining Lands Management, 2016)
Soil moisture stress in coffee plant impacts on the productivity of coffee fruit at PT. Perkebunan Nusantara XII, it is because the low ability of the soil to store water. The ability of the soil to store water can be increased by increasing the organic matter content of soil, especially humic substances. Soil organic matter plays an important role in the improvement of soil physical properties, especially the availability of soil moisture for plants. The purpose of this study was to analyze several humification parameters at four age of plantations plots of coffee and its relation to the water distribution potensial on Inceptisol PT. Perkebunan Nusantara XII Malang district. The research was conducted at PT. Perkebunan Nusantara XII were taken soil samples from 8, 28, 40, and 80 years old robusta coffee plots at 0-30 cm and 30-60 cm soil depth. The results showed that the increasing the age of the coffee plantations significantly increased the input of organic matter in the soil, with indicators of increased litter on soil surface, increased levels of soil C-organic and N-total, humic acid and soil pH. Increasing age of coffee plantations until 80 years did not affect to the value of humification parameters (C/N ratio, HA/FA ratio, E4/E6 ratio, and the humification rate (HR)). The age of coffee plantations affected the total acidity, carboxylic groups and phenolic OH, where the values tended to decrease with the  older of coffee plantations in the 0-30 cm of soil layers and increased in 30-60 cm. Increasing age of coffee plantations improved the total pores and available water content in the 0-30 cm of soil layer.